Working Capital Efficiency Assistance for Food and Beverage Vendors - Muh. Ramli; Arianto Dangkeng; Hasrul Wijaya; Nengsi Sudirman; Afrianto; Andini (www.amertainstitute.com, 2025)
This community engagement program aims to enhance the efficiency of working capital management among food and beverage vendors operating around Lapangan Pancasila Palopo. Efficient working capital management is essential for maintaining business continuity, sustaining daily operations, and improving profitability, especially for micro and small enterprises with limited financial resources. The program focused on three key components of working capital: inventory control, cash flow optimization, and the management of accounts receivable and payable. Through socialization activities, mentoring, and the establishment of a task force, participants were introduced to practical approaches such as the First In, First Out (FIFO) method, Just in Time (JIT) purchasing, negotiation strategies with suppliers, and the adoption of basic financial technology tools, including point-of-sale systems and simple accounting applications. The results demonstrate an increased understanding among vendors regarding cost efficiency, inventory planning, and the importance of disciplined financial recording. Vendors also reported improvements in cash flow stability, reduced operational waste, and better allocation of resources for both short-term and long-term needs. Furthermore, the program strengthened their ability to maintain product quality and price competitiveness, ultimately enhancing business sustainability. Overall, this activity provided significant benefits by equipping vendors with practical skills and strategies to manage working capital more effectively and to improve their resilience in a highly competitive market.